Textbooks illustration features for junior schoolchildren in the establishment of state independence of Ukraine period (1990-2000) - Ivanna Pohonets (Kazimierz Wielki University, 2020)
The article considers the peculiarities of illustrating school textbooks for primary schools ofUkraine, published in 1990-2000 inthe second half of the twentieth century in the context of reforming the national school system, development school textbook theory and the art of book graphics. Illustrative material of a number of outlined textbooks is analyzed period according to didactic, hygienic and artistic and aesthetic criteria and corresponding quality indicators of this structural component textbook. The main trends in illustrating publications for junior schoolchildren during the period of state independence ofUkraine. The relevance of taking into account positive ideas in illustration is argued educational publications of 1990-2000 in the process of creating a visual series for textbooks in the future.